WHAT ARE THE EFFECTS OF TITANIUM DIOXIDE AND ALUMINUM ON THE BRAIN? - Zaripova O.O. , (Central Asian Journal of Medicine, 2025)
Synthetic food colorants are organic compounds that do not occur naturally, meaning they are artificially produced. Most of them have been used in the global food industry for decades. Many of these colorants form insoluble complexes (lakes) with metal ions and, in this form, serve as pigments for coloring powdered products, dragees, tablets, and chewing gum. Unlike natural food colorants, synthetic ones do not exhibit biological activity and do not contain flavoring compounds or vitamins. However, they offer significant technological advantages over natural colorants, as they are less sensitive to processing and storage conditions while providing bright, easily reproducible colors [7], [8], [9].